Role of Nuclear Factor Kappa B (NF-κB) Signalling in Neurodegenerative Diseases: An Mechanistic Approach - SINGH, Shareen; SINGH, Thakur Gurjeet (Current neuropharmacology, 2020)
A transcriptional regulatory nuclear factor kappa B (NF-κB) protein is a modulator of cellular biological activity via binding to a promoter region in the nucleus and transcribing various protein genes. The recent research implicated the intensive role of nuclear factor kappa B (NF-κB) in diseases like autoimmune disorder, inflammatory, cardiovascular and neurodegenerative diseases. Therefore, targeting the nuclear factor kappa B (NF-κB) protein offers a new opportunity as a therapeutic approach. Activation of IκB kinase/NF-κB signaling pathway leads to the development of various pathological conditions in human beings, such as neurodegenerative, inflammatory disorders, autoimmune diseases, and cancer. Therefore, the transcriptional activity of IκB kinase/NF- κB is strongly regulated at various cascade pathways. The nuclear factor NF-kB pathway plays a major role in the expression of pro-inflammatory genes, including cytokines, chemokines, and adhesion molecules. In response to the diverse stimuli, the cytosolic sequestered NF-κB in an inactivated form by binding with an inhibitor molecule protein (IkB) gets phosphorylated and translocated into the nucleus further transcribing various genes necessary for modifying various cellular functions. The various researches confirmed the role of different family member proteins of NF-κB implicated in expressing various genes products and mediating various cellular cascades. MicroRNAs, as regulators of NF- κB microRNAs play important roles in the regulation of the inflammatory process. Therefore, the inhibitor of NF-κB and its family members plays a novel therapeutic target in preventing various diseases. Regulation of NF- κB signaling pathway may be a safe and effective treatment strategy for various disorders.